Does climacteric status impact regulation of the autonomic nervous system at the age of 46 years?. (2nd November 2022) - Salin, S.; Savukoski, S.; Tulppo, M.; Pesonen, P.; Auvinen, J.; Suvanto, E.; Puukka, K.; Niinimäki, M.
Abstract: Objective: To investigate whether an earlier-onset climacteric phase is associated with autonomic imbalance at the age of 46 years. Methods: This cross-sectional birth cohort study included 2661 women aged 46 years. Participants were divided into climacteric ( n  = 359) and preclimacteric ( n  = 2302) groups based on menstrual history and follicle stimulating hormone values. The mean heart rate (HR), low-frequency (LF) power, high-frequency (HF) power and LF/HF ratio were analyzed from heart rate variability recordings. The variables were compared between the groups using multivariable linear regression models, including body mass index, smoking and physical activity. The effects of hormone therapy and hot flashes on autonomic function were evaluated in sub-analyses. Results: Climacteric women had a lower mean HR in seated (71.9 ± 10.5 vs. 72.6 ± 10.4 bpm, p  = 0.015) and standing (81.2 ± 12.8 vs. 83.6 ± 12.1 bpm, p  = 0.002) positions compared to preclimacteric women, and the differences remained significant after the adjustments. In the sub-analyses, more frequent hot flashes were associated with a lower LF power and LF/HF ratio in the sitting position. Conclusions: The present study suggested an association between greater parasympathetic activation in women with more advanced climacteric status at the age of 46 years.